2013
DOI: 10.1186/1471-2334-13-235
|View full text |Cite
|
Sign up to set email alerts
|

Planning and process evaluation of a multi-faceted influenza vaccination implementation strategy for health care workers in acute health care settings

Abstract: BackgroundInfluenza transmitted by health care workers (HCWs) is a potential threat to frail patients in acute health care settings. Therefore, immunizing HCWs against influenza should receive high priority. Despite recommendations of the World Health Organization, vaccine coverage of HCWs remains low in all European countries. This study explores the use of intervention strategies and methods to improve influenza vaccination rates among HCWs in an acute care setting.MethodsThe Intervention Mapping (IM) method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 20 publications
0
18
0
1
Order By: Relevance
“…The intervention and external group were allowed to make their own choices and decisions regarding the implementation of programme elements. An evaluation of the process showed that intervention and external UMCs targeted most of the behavioural determinants and choose to implement a variety of the developed methods, whereas the control UMCs targeted less determinants [18], Figure. However, actual exposure of HCWs to these methods was variable and in 2009 largely affected by the pandemic preparedness plans. Lead contacts from the control group did not receive the developed methods and were encouraged to follow their usual influenza vaccination policy.…”
Section: Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intervention and external group were allowed to make their own choices and decisions regarding the implementation of programme elements. An evaluation of the process showed that intervention and external UMCs targeted most of the behavioural determinants and choose to implement a variety of the developed methods, whereas the control UMCs targeted less determinants [18], Figure. However, actual exposure of HCWs to these methods was variable and in 2009 largely affected by the pandemic preparedness plans. Lead contacts from the control group did not receive the developed methods and were encouraged to follow their usual influenza vaccination policy.…”
Section: Interventionmentioning
confidence: 99%
“…An 11-item prediction model with nine behavioural and two demographic predictors could be developed that was highly accurate in discriminating vaccinated from non-vaccinated staff in approximately 95% of the study population. Subsequently, we used the Intervention Mapping (IM) method to thoroughly plan, develop and evaluate a programme that was directed at HCWs in order to influence their behaviour towards immunisation [15,18]. This IM method is a theoretical framework to systematically develop health education interventions and can be used as part of the dynamic process of planning intervention strategies in health education.…”
Section: Interventionmentioning
confidence: 99%
“…D'autres programmes ont visé la prévention des déficits auditifs chez les agriculteurs [70], la promotion de l'activité physique et de la relaxation en entreprise [71], ou la promotion de la vaccination contre la grippe chez les professionnels de santé [72]. Ce protocole a été utilisé dans des populations adultes, des populations d'enfants, d'adolescents et d'étudiants, des populations gériatriques, ou encore des populations défavori-sées sur le plan socioéconomique ou de la santé mentale.…”
Section: Variété Des Applicationsunclassified
“…For acute care settings, which treat patients during epidemics, the number of trials is limited. As these settings were not applicable to acute care settings, Riphagen et al performed a trial in acute care settings in the Netherlands …”
Section: Introductionmentioning
confidence: 99%
“…As these settings were not applicable to acute care settings, Riphagen et al performed a trial in acute care settings in the Netherlands. 7,23 Moreover, while influenza immunization is safe and relatively cheap, evidence on the economic benefits is not widely available for various healthcare settings, but this is an important aspect for hospital managers and policymakers to support such a program. 24 To get a better understanding of the health economic benefits of a vaccination program for healthcare workers, we performed a modeling study using as much input as possible from a clinical trial and complemented information with additional data not provided by the trial.…”
mentioning
confidence: 99%